2013
DOI: 10.1155/2013/740182
|View full text |Cite
|
Sign up to set email alerts
|

May-Thurner Syndrome: A Case Report and Review of the Literature

Abstract: May-Thurner syndrome (MTS) has been recognized as a clinical entity for almost six decades. The true incidence rate of MTS is unknown and perhaps ranges from 22 to 32% according to the autopsy studies in the early twentieth century. However, MTS related deep venous thrombosis (DVT) accounts for only 2%-3% of all lower limb DVTS. In MTS, the left common iliac vein is compressed against the fifth lumbar vertebrae by the right common iliac artery, as it crosses in front of the vein. Chronic pulsation of the arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 14 publications
0
50
0
3
Order By: Relevance
“…However, due to the advancement in surgical technology, less invasive techniques such as endovascular repair became widely accepted [1]. Following thrombolysis and cyst removal, we deployed an endovascular stent into the left CIV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the advancement in surgical technology, less invasive techniques such as endovascular repair became widely accepted [1]. Following thrombolysis and cyst removal, we deployed an endovascular stent into the left CIV.…”
Section: Discussionmentioning
confidence: 99%
“…May-Thurner Syndrome (MTS) is an anatomical variant of the venous system in which the left common iliac vein (CIV) is compressed by the overlying right common iliac artery (CIA) leading to (via an unknown mechanism) vessel wall injury and predisposition to thrombosis [1][2].…”
Section: Introductionmentioning
confidence: 99%
“…10 This chronic compression leads to intimal hyperplasia, caused by deposition of elastin and collagen, which creates the potential for venous stasis and subsequent thrombosis. 11 Furthermore, a recent case-control study suggested that compression greater than 70% is required in order to be an associated factor for left sided DVTs. 12 Although MTS has been shown to be present in about 20% of the population, it is thought to account for only 2% to 3% of all lower extremity DVTs.…”
Section: Risk Factorsmentioning
confidence: 99%
“…24,25 It is suggested that the anatomical defect should be repaired with the use of stents and balloon venoplasty. 11 Patients with a high clot burden should also undergo inferior vena cava filter placement. 25 …”
Section: Managementmentioning
confidence: 99%
“…From autopsy studies, MTS accounts for 2-3% of lower limb deep vein thrombosis [2]. However; it is often underreported and miss-diagnosed in accident and emergency, resulting in long-term complication (post thrombotic syndrome) with its detrimental effect [3].…”
Section: Introductionmentioning
confidence: 99%